Pain and daily activities in rheumatoid arthritis - Ahlstrand, I.; Bjork, M.; Thyberg, I.; Borsbo, B.; Falkmer, Torbjorn (Informa Healthcare, 2012)
Aim: The aim of this study was to describe experiences of pain and its relationship to daily activities in people with rheumatoid arthritis (RA). Method: Seven semi-structured focus group discussions were conducted with 33 men and women of different ages with RA. Data were analysed with content analysis. Results: Pain affected everyday life and may be a barrier to perform valued activities. Regarding the impact of pain on participation and independence, personal factors and the social environment were found to be important. It could be a struggle to find the right activity balance, since it was easy to be overactive, triggering subsequent elevation of pain levels. However, the participants also described activities as a mediator of pain and a distraction from it. Conclusion: The relationship between pain and daily activities in RA was complex. Pain as an impairment was expressed to be related to activity limitations and participation restrictions, as well as to contextual factors. These findings highlight the clinical importance of paying attention to the complexity of pain and its relation to daily activities and participation.